KEWENANGAN PEMERINTAH DAERAH PROVINSI DALAM MENERBITKAN IZIN PERTAMBANGAN BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Elvalina, Dedis; Firdaus, Emilda; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
National Constitution Number 23 on 2014 about Regional Government mandated that the implementation of government affairs in energy and mineral resources are divided between the central government and the provinces. Including the authority to issu the permits for mineral and coal. Before the enactment of National Constitution Number 23 on 2014 about Regional Government, the mining permit issuing authority is divided between the government, the provincial government, and local government of district/city. Now all authority to issue the permits that were previously owned by the district/city, is now owned by the provinces.This raises the pros and cons in the community. Some of them agree that the authority to issue the mining permits that were previously owned by the distric/city is now transferred to the provinces, and there are others that doesn’t agree, and there are also some of them asking that such authority to be returned to the district/city.Key Words: Authority – Autonomy – Mining Permit